Perceived societal view about condom use and risky sexual behaviour of never-married in-school adolescents in Ibadan, Nigeria (2019)
There are social factors, within the adolescent environment, that hinder condom use, in HIV prevention. It is therefore important to understand the perception of never-married adolescents towards societal support for condom use, the effectiveness of condoms and access to them. This study assessed the relationship between perceived societal views on condom use and the risky sexual behaviours of adolescents in secondary schools in Nigeria. An interviewer-assisted questionnaire was used to collect information from 420 never-married adolescents, in selected secondary schools, in Ibadan North-East local government area. Perceived societal view about condom use was assessed under support, effectiveness, access. Chi-square and logistic regression were used for data analysis at p<0.05. Mean age of the respondents was 14±1.54 years while 43.3% were males and 19.3% were sexually experienced. Seventy-two (17.8%) perceived societal high support for condom use, 150 (37.3%) believed condom was highly effective and 67(16.5%) had good access to condom. Males were more likely to perceive high support for condom use (AOR=3.17; 95% CI: 1.843-5.433) and high condom effectiveness (AOR=1.57; 95% CI: 1.036-2.374). Perceived support for condom use was significantly associated with multiple sexual partners, sexual activity under the influence of drugs and alcohol (AOR=4.19; 95% CI: 1.752-10.044, AOR=3.67, 95% CI: 1.524-8.851 and AOR=3.91, 95% CI: 1.598-9.575). Sexually experienced adolescents perceive more social support for condom use but had low perception about their access to condom and its effectiveness. Behavioural change efforts promoting condom use as a means of preventing consequences of unprotected sex including HIV should encourage societal acceptance for condom use among adolescents and support access to it as well.